Application of the Milan System for Reporting Salivary Gland Cytopathology with Histopathological Correlation - Baral, Alina; Pradhan, Anju; Upadhyaya, Paricha; Paudel, Ashish (International Journal of Silkroad Institute of Research and Training, 2024)
Background: Fine-needle aspiration (FNA) is widely accepted as an efficient first line diagnostic of salivary gland lesions. Intratumoral heterogeneity and morphological overlap existing between salivary gland tumors makes it rigorous and challenging in the diagnosis by FNA. The Milan System for Reporting Salivary Gland Cytopathology (TMSRSGC) is a tiered risk-stratification scheme designed to standardize reporting and facilitate decision making. The objective of this study is to evaluate the efficacy of The Milan system for reporting salivary gland cytopathology with histopathological correlation. Method: A prospective study of salivary gland cytology was performed over a 1-year period at Department of Pathology BPKIHS. Cases were categorized as per the MSRSGC and histopathological correlation was obtained. The risk of malignancy were calculated for all diagnostic categories. Result: A total of 30 salivary gland cytology with histopathological follow up were evaluated. FNA had a sensitivity, specificity, diagnostic accuracy, PPV and NPV of 72.7%, 100%, 88.88%, 100% and 84.2% respectively. Good agreement was seen between cytological and histopathological diagnosis. Conclusion: The Milan System for Reporting Salivary Gland Cytopathology provides an effective standardized diagnostic framework which aids in better clinicopathological communication and improves the quality, clarity as well as reproducibility of cytological diagnosis of salivary gland lesions.